Clinical and aetiological study of chronic lower limb ulcers - Kuntoji, Shrikant B.; Guduru, Pavan Kumar (International Surgery Journal, 2021)
Background: Chronic ulceration of the lower leg is a frequent condition, with a prevalence in the population over 60 years of age. The incidence of ulceration is rising as a result of the ageing population and increased risk factors for atherosclerotic occlusion such as smoking, obesity and diabetes. Ulcers can be defined as wounds with a ‘full thickness depth’ and a ‘slow healing tendency”. In general, the slow healing tendency is not simply explained by depth and size, but caused by an underlying pathogenetic factor that needs to be removed to induce healing. The main causes are venous valve insufficiency, lower extremity arterial disease and diabetes, less frequent conditions are infection, vasculitis, skin malignancies and ulcerating skin diseases such as pyoderma gangrenosum. For a proper treatment of patients with leg ulcers it is important to be aware of the large differential diagnosis of leg ulceration and to effectively manage the conditions. Methods: Prospective study of 80 cases of chronic lower limb ulcers admitted at S. Nijalingappa medical college and HSK hospital and research centre, Bagalkot during the period January 2019 to June 2020, with regular dressings, debridement, skin grafting’s, amputations, treating underlying systemic diseases were done. Results: In a study of 80 cases, most of the patients with lower limb ulcers had an underlying systemic disease like diabetes, vascular insufficiency both arterial and venous. Conclusions: In a prospective study of 80 patients having chronic lower limb ulcers the commonest ulcer was diabetic foot ulcers followed by arterial/ischemic ulcers. The highest incidence is seen in sixth decade of life with male predominance.